1996
DOI: 10.1073/pnas.93.17.9297
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of a gene involved in constitutive, high-affinity nitrate transport in higher plants.

Abstract: Two mutations have been found in a gene (NRT2) of Arabidopsis thaliana that specifically impair constitutive, high-affinity nitrate uptake. These mutants were selected for resistance to 0.1 mM chlorate in the absence of nitrate. Progeny from one of the backcrossed mutants showed no constitutive uptake of nitrate below 0.5 mM at pH 7.0 in liquid culture (that is, within 30 min of initial exposure to nitrate). All other uptake activities measured (high-affinity phosphate and sulfate uptake, inducible high-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…The severe defect of cHATS in the nar2.1 mutant [65], but not the nrt2.1 nrt2.2 double mutant [28], suggested that another NRT2 gene(s) was probably responsible for cHATS. A mutant defective in cHATS, chl8, was isolated by chlorate selection at low concentration [66], but the gene mutated in chl8 has not been identified. It will be interesting to determine whether one of the NRT2 genes, particularly NRT2.6 or NRT2.7, both of which are constitutively expressed in root [67,68], is responsible for the chl8 phenotype.…”
Section: Genes Involved In High Affinity Nitrate Uptake (Hats)mentioning
confidence: 99%
“…The severe defect of cHATS in the nar2.1 mutant [65], but not the nrt2.1 nrt2.2 double mutant [28], suggested that another NRT2 gene(s) was probably responsible for cHATS. A mutant defective in cHATS, chl8, was isolated by chlorate selection at low concentration [66], but the gene mutated in chl8 has not been identified. It will be interesting to determine whether one of the NRT2 genes, particularly NRT2.6 or NRT2.7, both of which are constitutively expressed in root [67,68], is responsible for the chl8 phenotype.…”
Section: Genes Involved In High Affinity Nitrate Uptake (Hats)mentioning
confidence: 99%
“…HATS consists of two systems, the nitrateinducible HATS (iHATS) and the constitutive HATS (cHATS) (Wang and Crawford 1996, Crawford and Glass 1998, Forde 2000. In Arabidopsis thaliana, seven genes were isolated as NRT2 family gene members (Orsel et al 2002b), suggesting that NRT2 in higher plants is composed of several genes.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen uptake is affected by changes in the N content or composition in the media (Wang and Crawford 1996;Morgan and Jackson 1988;Foulkes et al 1998) and carbohydrate (Champigni and Tolouizte 1986) within the root as well as by N demand of the shoot (Imsande and Touraine 1994). Nitrogen uptake in plants i.e.…”
Section: Mineral Acquisition By the Plantmentioning
confidence: 99%